Efek Biblioterapi Dalam Menurunkan Kecemasan Pada Anak Usia Sekolah (7 – 12 tahun) Saat Perawatan Di Rumah Sakit - Badrul Munif; Akhmad Yanuar Fahmi Pamungkas; Atik Pramesti Wilujeng; Yusuf Waliyyun Arifuddin; rudiyanto rudiyanto (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Background: The child has difficulty in understanding why they are sick, hospitalization can cause separation anxiety in children, which includes protest, despair, discharge, loss of control so it needs bibliotherapy. Bibliotherapy is the use of the book as a medium of therapy to minimize stressors, prevent the loss, reduce anxiety, and support children coping. Aims: The purpose of this study was to determine the effect Biblio therapy against anxiety levels in school-age children (7-12 years) in the Children's Room of Blambangan Banyuwangi Hospital. Methods: Pre-experimental research design using the technique of one group pre-post test design. A sample of 20 children with accidental sampling technique. Data obtained from observations before and after giving bibliotherapy, and then do the scoring, tabulating, and statistical tests using Wilcoxon match pair test. Results: Manually obtained calculation number 199> 52 = Ho is rejected and Ha is accepted, meaning that there are differences in anxiety levels before and after biblio therapy which means there is a significant effect of bibliotherapy on anxiety levels in school-aged children (7–12 years) in the Children's Room of Blambangan Hospital Banyuwangi. Conclusions: Billion therapy can be applied as one of the nursing interventions in the hospital to decrease the problem of children to keep children happy and cooperative during hospitalization.